(3LhgQI GdHjGf aj fSH GdSjOI bVjH GdHGfs - (3CHhQHjYI YjSi GdMSfj GdehUdjs; (3CHh QHjYI YjSi GdMSfj GdehUdj,J (B573 (3g` s
(3ChdgG (B:s
(3hHYO abO SCdfj CHhSYjO GdMSf Hf CHj YRjR ai MOhO SfI (B901 (3Cf CLeY TjFkG ef efGbH GdSjO GdTQja GdMSfj GdMSjfj GdYGQa HGddg s
(3BNQgG (B:s
(3fYhP HGddg SHMGfg ef Pdc , hCHQC Edjg eeG dGjQVjg hGdMeO ddg QH GdYGdejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B147 s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI HZOGO (B(541) s
Keywords: (3GdJGQjNs